The Relevance of Arabic Language Learning According to Rusydi Ahmad Thu'aimah with Modern Education Strategies - Rania Izzati; Rahmat Hidayat Lubis; Nabil Fuadi; Shafwatul Widad (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2025)
Arabic language learning has a strategic role in shaping students linguistic competence, especially in the context of Islamic education. Along with the development of globalization era and demands of modern education, the conventional approach in learning Arabic is often considered less relevant. In response to this issue, Rusydi Ahmad Thu'aimah an expert in Arabic language education, offers learning strategies that are adaptive, innovative, and in accordance with the principles of modern education. This study aims to analyze the relevance of Thu'aimah's ideas to modern educational strategies through descriptive-analytical literature study method. The main findings show that Thu'aimah's focus on student-centered and communicative learning is in line with modern approaches, which encourage a more interactive and practical language learning environment. Moreover, his emphasis on the use of technology and media in language teaching is increasingly relevant in this digital era. This paper provides an insight into how educators can integrate traditional principles of Arabic language teaching with contemporary methods to enhance the language learning process. The approach offered by Thu'aimah can be the basis for updating Arabic language learning strategies to be more effective in accordance with the demands of the times. This research can be a reference for future in-depth research. However, this study is limited by its lack of empirical evidence and practical application in its discussion. Future research can focus on field studies to test the implementation of Thu'aimah's concepts in various educational contexts both in schools and other institutions, especially in the digital era.